Liminal traces storying, performing, and embodying postcoloniality - Chawla, Devika; Rodriguez, Amardo; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
Home and exile have become key discussions in discourses of globalization, cosmopolitanism, postcolonialism, transnationalism, identity, and multiculturalism. These discourses can be expected to flourish in the future as an increasing number of multicultural scholars struggle with various kinds of displacements and the meaning of home that is thereby instantiated anew as we experience living in between cultures. This book sits in the intersection between cultural studies and performance studies. It seeks to break theoretical and empirical ground by reframing understandings of home and exile. Popular notions of exile forwarded by transnational and postcolonial scholars position home as a place of return and longing. While we believe that there are many truths in this position, we performatively seek emergent forms of displacement that are demanding new frameworks with which to enact meanings of home and exile. As Third World immigrant scholars in Western academe, we believe our move is vital in order to explore the experiences of persons, such as ourselves, who fall outside the models of displacement that have long constituted émigré writings. We define this move as a performative one because we experiment with different genres and voices to question and reproblematize existing understandings of knowledge frames. The genres we embody include performative writing, dialogue, autoethnography, essay form, personal narrative, and so on. Our goal is to address theories, stories, and pedagogies that speak to our tribulations in negotiating such intellectual displacements. This book can be an ideal supplementary text for courses in cultural studies as every chapter speaks in performative, reflexive, and storied ways to our own struggles to find real and theoretical homes. It will therefore have relevance to many departments in the humanities, including Communication Studies, English, Cultural Studies, Education, Anthropology, Sociology, and Women's Studies. In fact, this book serves the heuristic function of inspiring new research questions and demonstrating how a wide range of theories and research methods can be employed to enact discourses of home and exile. - Publisher's description.
Electronic reproduction.
Keywords: Postcolonialism; Culture; Immigrants; Electronic books